Tunable Beam Steering Metasurface Based on a PMN-PT Crystal with a High Electro-Optic Coefficient - Huan Chen; Zixin Wang; Xin Chen; Junli Wang (Sensors)
Existing tunable optical metasurfaces based on the electro-optic effect are either complex in structure or have a limited phase modulation range. In this paper, a simple rectangular metasurface structure based on a Pb(Mg1/3Nb2/3)O3-PbTiO3 (PMN-PT) crystal with high electro-optic coefficient of 120 pm/V was designed to demonstrate its electrically tunable performance in the optical communication band through simulations. By optimizing the structure parameters, a tunable metasurface was generated that can induce a complete 2π phase shift for beam deflection while maintaining relatively uniform transmittance. Simulations further demonstrated the electrical tunability of the beam deflection direction and operating wavelength of the metasurface. This tunable optical metasurface, with its simple and easily fabricated structure, can promote the development and application of multifunctional and controllable metasurfaces. Its adjustable beam deflection direction and operating wavelength may find applications in fields such as optical communication systems and imaging.